RANCANG BANGUN SISTEM INFORMASI REKRUTMEN KARYAWAN BARU BERBASIS WEB PADA PT. MANDIRI ANDALAN UTAMA - Evy Nurmiati; Muhammad Sharhan Khatami (Jurnal Teknologi Informasi dan Komputer, 2025)
PT Mandiri Andalan Utama still relies on external platforms such as Glints and Job Street in the recruitment process, so that applicant data management is less than optimal and selection is slow. To overcome this, this study developed a web-based recruitment information system with the Rapid Application Development (RAD) method through the planning, design, and implementation stages, with UML tools for structure visualization and black-box testing to ensure optimal functionality. This system successfully accelerated the process through online registration, automatic data management, real-time monitoring of selection status, and database integration, which proved to be more efficient than conventional methods. In the future, the system can be enhanced with the integration of artificial intelligence (AI) for automatic selection and smarter HR analysis, so that PT Mandiri Andalan Utama can optimize recruitment efficiency, support company growth, and develop more advanced HR technology strategies.